Analisis Perbaikan Dan Perancangan Pada Kursi Penjahit Secara Ergonomis Dengan Metode Quality Function Deploymeny (QFD) Dan Antropometri Di CV Cahaya Setia Mulia - Mardy, Dinda Oe; atmaja, Jastika Amelia; Saputro, Wisnu Saputro; Yuliandana, Reihan Bintang; Mawardah, Melysa Putri; Ayudyah Eka Apsari (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2025)
CV Cahaya Setia Mulia is a company engaged in the service and production of sports gloves. June-October 2024 production data, the demand for gloves increased significantly, from 3,850 pcs in May to more than 5,000 pcs, so tailor workers are expected to produce products quickly and do repetitive work for a long time. The chairs used by workers are plastic chairs without backrests. This research uses the Nordic Body Map questionnaire, Anthropometric method, and Quality Function Deployment (QFD) approach. Based on the results of the NBM questionnaire, the complaints felt by 16 workers were obtained, namely that the average worker had the highest complaints in low back pain with an average of 2.1 pain in the right shoulder, pain in the right thigh, pain in the right knee, pain in the right ankle, pain in the right foot with an average value of 1.9, pain in the left knee and pain in the bronze with an average value of 1.8. A QFD approach was applied to ensure the chair design met customer needs. As a result, four key attributes were identified: the chair has a backrest, foam on the backrest and seat, neutral color, and quality material from mahogany wood. Based on Anthropometric calculations from 5 tailor workers, the seat size for the seat width is 49.8 cm, seat height is 35 cm, seat length is 44.2 cm, seat back length is 60.9 and seat elbow base height is 26.9 cm. Sewing chair design using Autodesk Fusion software.